Effect of undisturbed ground temperature on the design of closed-loop geothermal systems: A case study in a semi-urban environment. (15th August 2017) - Radioti, G.; Sartor, K.; Charlier, R.; Dewallef, P.; Nguyen, F.
Highlights: High-resolution ground temperature profiles and comparison with numerical results. Error in ground temperature estimation from TRT data and impact on the design. Optimisation of BHEs design in urbanised areas. Abstract: This paper presents temperature measurements in four Borehole Heat Exchangers (BHEs), equipped with fiber optics and located in a semi-urban environment (campus of the University of Liege, Belgium). A 3D numerical model is also presented to simulate the heat loss from the surrounding structures into the subsurface. The mean undisturbed ground temperature was estimated from data during the preliminary phase of a thermal response test (water circulation in the pipe loops), as well as from borehole logging measurements. The measurements during water circulation can significantly overestimate the ground temperature (up to 1.7 °C in this case study) for high ambient air temperature during the test, resulting in an overestimation of the maximum extracted power and of the heat pump coefficient of performance (COP). To limit the error in the COP and the extracted power to less than 5%, the error in the undisturbed temperature estimation should not exceed ±1.5 °C and ±0.6 °C respectively. In urbanised areas, configurations of short BHEs (length < 40 m) could be economically advantageous (decreased installation and operation costs) compared to long BHEs, especially for temperature gradient lower than −0.05 °C/m.